FENOMENA INSOMNIA SEBAGAI RANGSANG PENCIPTAAN KARYA TARI TIDAK TIDUR - Prasika Dewi Nugra (Puitika, 2018)
The concept chosen as the basis of cultivation in the form of abstraction from the movement of individuals and groups who experience insomnia and who do work at night and visualization of the movement that occurs continuously by human activities on the surface of the earth such as rotating. This work was inspired by the phenomenon of insomnia, worked on the theme of life and abstract type by cultivation method done through field observation, motion exploration, evaluation, and the manifestation of the work. The first part ignores the movement of individual and group activities that are experiencing insomnia. The second part describes the night activities of the workers at night. The third part is to visualize how the imagination of human activity that occurs constantly day and night is like rotating. Keywords: choreography, insomnia, night worker, time utilization